Improvements of Thermochemical Properties of Corn Biomass by Torrefaction Process - Khempila, Jarunee; Kongto, Pumin (Journal of Advanced Development in Engineering and Science, 2021)
In Thailand, post-harvest burning of corn stover residue is a preferred practice, causing particulate matter emissions and air pollution. To curtail this problem, converting them to value-added products such as solid fuel is desirable. In this research, the effects of torrefaction temperature on the physical and chemical properties of corn stover (Corn leave and straw) were investigated. The reaction temperatures were between 250°C and 300°C. The results indicated that with an increase in the torrefaction temperature, the mass yield and energy yield decreased from 79.85 and 87.62% at 250°C to 47.40 and 63.36% at 300°C, respectively. While found an increase in energy densification from 9.56 % to 33.68 %. In addition, increasing torrefaction temperature, the moisture content of the samples reduced. Resulting in an increase in the combustible forms which is in line with the reduction of the number of hydroxyl groups (O-H), the hydrogen and oxygen content, while the fixed carbon fraction in the sample increases to 59.65% derived at 300 °C. The H/C and O/C ratios calculated at 300°C indicated that the value was closer to Lignite. Additionally, the higher heating value of raw corn stover improved significantly from 19.60 MJ/kg to 23.80 MJ/kg derived at 300°C. Based on this study, thermochemical torrefaction has the potential of improving corn stover as solid biofuels.